Poverty and Material Deprivation among the Self-Employed in Europe: An Exploration of a Relatively Uncharted Landscape - Jeroen Horemans; Ive Marx (Institute of Labor Economics (IZA), 2017)
In work-poverty has become a pressing social issue in Europe. The self-employed remain relatively uncharted terrain in this context. With about 15 percent of European workers in self-employment this group can no longer be ignored, especially since self-employment is on the rise in many countries, particularly own-account self-employment. Drawing on EU-SILC data this paper provides a systematic mapping exercise of poverty and living standards among the self-employed in the European Union. We find that the self-employed in Europe generally face significantly higher income poverty risks than contracted workers. Looking in more detail at the drivers of income poverty among the self-employed we find that in addition to lower reported earnings, lower overall work-intensity at the household level appears to be an important driver. However, while income poverty levels are quite significant among the self-employed, material deprivation rates are generally much lower. The discrepancy between income poverty measures and material deprivation measures is much larger for the self-employed than it is for employees. One possible explanation is that the self-employed can more often draw on assets accumulated over the life cycle or on business assets they control. The self-employed constitute a very mixed segment of the workforce and within-group inequality is quite significant. One group emerges as being particularly at-risk of poverty are own-account workers, substantiating worries about the rise of this form of self-employment. While the paper offers extensive descriptive analysis and some tentative explanations, an important and sizable research agenda remains.
Keywords: I32; I38; J21; J22; L26; 330; in-work poverty; material deprivation; self-employment; Europe